2022
DOI: 10.3389/fpubh.2022.761904
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Body Mass Index With Mortality Among Pulmonary Hypertension Patients: A Systematic Review and Meta-Analysis of Cohort Studies

Abstract: ObjectiveTo run a systematic review and meta-analysis of related studies on body mass index (BMI) and the risk of death among pulmonary hypertension (PH) patients, as well as, to shed light on the shape and strength of the dose-response association.MethodsStudies published up to Jun 2021 in scientific databases such as Scopus, and PubMed as well as Google Scholar were searched. Cohort studies that reported risk estimates for at least two categories of BMI or per certain increase in BMI in relation to mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Our study findings were consistent with a study by Jiang et al, who also explored the link between obesity and mortality in patients with pulmonary hypertension [20]. In this meta-analysis consisting of 127,215 participants, the authors found that for every 5 unit increase in BMI, a risk reduction (RR 0.83 (95% CI 0.77-0.89)) in mortality was noted, with the lowest risk in those with BMI 32-38 kg/m 2 .…”
Section: Discussionsupporting
confidence: 94%
“…Our study findings were consistent with a study by Jiang et al, who also explored the link between obesity and mortality in patients with pulmonary hypertension [20]. In this meta-analysis consisting of 127,215 participants, the authors found that for every 5 unit increase in BMI, a risk reduction (RR 0.83 (95% CI 0.77-0.89)) in mortality was noted, with the lowest risk in those with BMI 32-38 kg/m 2 .…”
Section: Discussionsupporting
confidence: 94%